Agricultural Market Stability in the Future Common Agricultural Policy - Marilena, Niculescu Oana (Mediterranean Journal of Social Sciences, 2012)
Market stability represents one of the general objectives of the Common Agricultural Policy (CAP), reconfirmed by the LisbonTreaty. The purpose of this paper is to study the impact of market stability in the context of price volatility for the post-2013 CAP. Thepolitical and economical context in Europe highlights the need for a new approach to cope with market volatility in order to create astable business environment. The research method is the analysis of data with a view to express a personal opinion in this regard. Pricevolatility depends on several determinants like: balance between supply and demand, interlink between food and energy markets, tradeliberalization, environment and climate change. The negative effects generated by instability in the agricultural markets can be reducedthrough the development of the existing instruments, the use of new mechanisms to stabilize supply, price and income, markettransparency and cooperation. Farmers should adjust their business to market conditions and have to be protected against extremevolatility, innovation, education and training being important in this way. A special attention should be given to the interaction betweenthe objectives of Agenda 2020 and the CAP. The results of the research point out that market stability is important for the CAP post-2013and can be promoted using a combination of instruments like: modern technologies to stabilize yields, contracts, hedging, insurancesystems.